Population dynamics of Aceodromus convolvuli (Acari: Mesostigmata: Blattisociidae) on spontaneous plants associated with Jatropha curcas in central Brazil - Cruz, Wilton P. [UNESP]; Sarmento, Renato A.; Pedro-Neto, Marcal; Teodoro, Adenir V.; Rodrigues, Diego M.; Moraes, Gilberto J. de [UNESP] (Springer, 2014)
Spontaneously growing plants are commonly considered competitors of cultivated plants. Owing to the lack of specificity of many arthropods, spontaneous plants may be attacked by the same arthropods that attack cultivated plants and they may also harbor natural enemies of organisms harmful to cultivated plants. Aceodromus convolvuli Muma (Blattisociidae) has been reported recently in relatively large numbers in Tocantins state, central Brazil, mostly on Helicteres guazumifolia Kunth (Malvaceae). Very little has been reported about the population dynamics of blattisociid mites under field conditions. The objective of this work was to study the population dynamics of A. convolvuli in Gurupi, Tocantins state, to evaluate its possible interaction with associated mites. Monthly samples were taken from leaves of the 11 most abundant and frequent spontaneous plants in a Jatropha curcas L. (Euphorbiaceae) plantation. About 96.5 % of the specimens of A. convolvuli were collected in the rainy season. The patterns of variation of the population of A. convolvuli and of predators belonging to the family Phytoseiidae were similar, but A. convolvuli was much more numerous than all phytoseiid specimens combined. Highly significant correlations were observed between A. convolvuli densities and relative humidity or diversity of spontaneous plants. When only mites on H. guazumifolia were considered, highly significant correlation was also observed between densities of A. convolvuli and of mites of the family Tetranychidae. The results suggested that A. convolvuli could be a predator of tenuipalpid and/or tetranychid mites. Studies about its biology are needed to determine its preferred food sources and potential as biological control agent.
Keywords: Ecology; Predation; Biological control; Blattisociid mite